2023
DOI: 10.3390/ijms25010164
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteomic Investigation of Hg-Binding Proteins in Renal Tissue of Rats Exposed to Mercury Chloride

Emerson Carlos de Almeida,
Victor Diego Faria,
Felipe Dalmazzo Cirinêu
et al.

Abstract: Results obtained from rat studies indicate that, even at low concentrations, mercurial species cause harmful effects on the kidneys, by inducing the nephrotic oxidative stress response. In the present work, Hg-associated proteins were identified as possible mercury-exposure biomarkers in rat kidneys exposed to low mercury chloride concentrations for 30 days (Hg-30) and 60 days (Hg-60), using metalloproteomic strategies. The renal proteomic profile was fractioned by two-dimensional electrophoresis and the mercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In one noteworthy, recent study, rats were injected with Hg 2+ to deliver a total dose of 8.03 μg/kg over 60 days after which their kidneys were collected. The subsequent homogenization of the kidneys followed by the extraction of the cytosolic proteins allowed to analyze the obtained complex mixture by 2D-GE [ 111 ]. While this study revealed 13 upregulated proteins and 47 downregulated proteins compared with the control group, the excision of protein spots followed by their analysis for total Hg by graphite furnace atomic absorption spectrometry revealed 11 Hg-containing spots, some of which contained up to 750 ppm of Hg.…”
Section: Advances Into the Toxicological Chemistry Of CD 2+...mentioning
confidence: 99%
“…In one noteworthy, recent study, rats were injected with Hg 2+ to deliver a total dose of 8.03 μg/kg over 60 days after which their kidneys were collected. The subsequent homogenization of the kidneys followed by the extraction of the cytosolic proteins allowed to analyze the obtained complex mixture by 2D-GE [ 111 ]. While this study revealed 13 upregulated proteins and 47 downregulated proteins compared with the control group, the excision of protein spots followed by their analysis for total Hg by graphite furnace atomic absorption spectrometry revealed 11 Hg-containing spots, some of which contained up to 750 ppm of Hg.…”
Section: Advances Into the Toxicological Chemistry Of CD 2+...mentioning
confidence: 99%